IMPLEMENTASI METODE DEMONSTRASI DALAM PEMBELAJARAN FIKIH PADA MATERI WUDHU SISWA KELAS II DI SDIT AL-ISLAMIYYAH - Halimah, Nur; Dwi Basuki , Danang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of the demonstration method in fiqih learning on wudhu material for second-grade students at SDIT Al-Islamiyyah. This study used a qualitative descriptive approach. The research subject was the second-grade teacher at SDIT Al-Islamiyyah. Data were collected through interviews and documentation. The results showed that fiqih learning on wudhu material was conducted through two stages, namely theoretical explanation and direct practice using the demonstration method. The teacher explained the wudhu material and demonstrated the correct procedures of wudhu, after which students practiced it in turns. The implementation of the demonstration method made students more active, enthusiastic, and easier to understand the wudhu material compared to learning that only used the lecture method. Although there were challenges in time management and maintaining students’ concentration, the demonstration method was considered effective in helping students understand and practice the correct procedures of wudhu.